Psychiatric nurses’ knowledge of palliative care: current status and influencing factors - Liu, Cuixia; Liu, Xiulan; Yan, Xiashu; Chen, Xiaodong; He, Xucong; Liu, Jian; Zeng, Tianyu (Frontiers in Psychology, 2025)
ObjectiveThis study aims to assess the current status of palliative care knowledge and identify the factors influencing it among healthcare workers in mental health institutions. The goal is to establish a scientific foundation for advancing palliative care practices in mental health settings.MethodsFrom August to September 2024, a survey was conducted to assess psychiatric nurses’ knowledge of palliative care. The study involved nurses from 47 mental health organizations in Guangdong Province, using general information and The Palliative Care Quiz for Nursing. Influencing factors were analyzed using one-way analysis of variance and multiple regression analysis.ResultsA total of 625 psychiatric nurses completed valid questionnaires. The average score was 10.307 ± 3.305. Only 15.65% of nurses had attended palliative care training, while 29.39% demonstrated knowledge. It was significantly correlated with professional title (r = 0.164), marital status (r = 0.087), witnessing the death of a terminally ill patient or relative (r = 0.117), prior study (r = 0.164), willingness to engage in (r = 0.152), having children (r = 0.100), and performing cadaveric care (r = 0.086) (all with p < 0.05). Professional title (B = 0.497), academic qualification (B = 0.708), and witnessing the death of a terminally ill patient or relative (B = 0.932) significantly influenced it (all p < 0.05).ConclusionPsychiatric nurses demonstrate limited awareness of palliative care, with a low percentage having received relevant training. However, there are a large number of long-term hospitalized psychiatric patients, it is crucial to provide systematic and specialized palliative care training for psychiatric nurses.